Discover a wealth of knowledge at Westonci.ca, where experts provide answers to your most pressing questions. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Answer:
(f + g)(x) = x² + 4x - 4 ⇒ B
Step-by-step explanation:
Let us solve the question
∵ f(x) = 4x + 4
∵ g(x) = x² - 6
→ We need to find (f + g)(x) which means f(x) + g(x)
∴ (f + g)(x) = f(x) + g(x)
∵ f(x) + g(x) = (4x + 2) + (x² - 6)
∴ f(x) + g(x) = 4x + 2 + x² - 6
→ Add the like terms
∵ f(x) + g(x) = 4x + x² + (2 - 6)
∴ f(x) + g(x) = 4x + x² + (-4)
→ Remember (+)(-) = (-)
∴ f(x) + g(x) = 4x + x² - 4
→ Arrange the terms from greatest power of x
∴ f(x) + g(x) = x² + 4x - 4
∴ (f + g)(x) = x² + 4x - 4
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.